Factors Related to Non-participation in the Basque Country Colorectal Cancer Screening Programme - Solís-Ibinagagoitia, M.; Unanue-Arza, S.; Díaz-Seoane, M.; Martínez-Indart, L.; Lebeña-Maluf, A.; Idigoras, I.; Bilbao, I.; Portillo, I. (Frontiers in Public Health, 2020)
Background: Despite the high participation rates in the Basque Country, colorectal cancer screening programme (Spain), there is still a part of the population that has never participated. Since it is essential to ensure equal access to health services, it is necessary to identify the determinants of health and socio-economic factors related to non-participation in the screening programme. Methods: Cross sectional descriptive study including all invited population in a complete round between 2015 and the first trimester of 2017. Health risk factors available in medical records and their control have been analyzed using univariate and multivariate analyses. Results: 515,388 people were invited at the programme with a 71.9% of fecal immunochemical test participation rate. Factors that increase the risk of non-participation are: being men (OR = 1.10, 95% CI 1.09–1.12); younger than 60 (OR = 1.18, 95% CI 1.17–1.20); smoker (OR = 1.20, 95% CI 1.18–1.22); hypertensive (OR = 1.14, 95% CI 1.12–1.15) and diabetic (OR = 1.40, 95% CI 1.36–1.43); having severe comorbidity (OR = 2.09, 95% CI 2.00–2.19) and very high deprivation (OR = 1.15, 95% CI 1.12–1.17), as well as making <6 appointments to Primary Care in 3 years (OR = 2.39, 95% CI 2.33–2.45). Still, the area under the curve (AUC) indicates that there are more factors related to non-participation. Conclusions: The participation in the Basque Country colorectal cancer-screening Programme is related to some risk factors controlled by Primary Care among others. Therefore, the involvement of these professionals could improve, not only the adherence to the CRC screening, but also other health styles and preventive interventions.